Barriers to the Cervical Cancer Screening by CPC-28 Questionnaire: A Pilot Study - Svihrova, Viera; Kocsis, Lukas; jr, Jan Svihra; Szaboova, Veronika (Archives of Clinical and Biomedical Research, 2022)
Abstract not available in the source database.